Targeted molecular imaging - Welch, Michael J.; Eckelman, William C. (Boca Raton : Taylor & Francis, 2012)
"Covering the fundamental concepts of molecular imaging, this work addresses basic principles, disease models, imaging studies in animals, imaging in initial human studies, and the application of molecular imaging in pharmacy and drug discovery. Topics are presented in logical progression, from basic concepts to applications. The text includes examples from human studies with imaging of breast cancer, cardiovascular disease, and neurodegenerative diseases. The book is a valuable tool for readers involved with molecular imaging, biomedical imaging, radiology, medical physics, medicinal chemistry, and pharmacology"--Provided by publisher.
pt. 1. In vitro studies -- pt. 2. Small animal studies -- pt. 3. Radiopharmacology and radiopharmacy -- pt. 4. Case studies on developing targeted nonnuclear probes -- pt. 5. Case studies on developing targeted radiotracers.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Molecular diagnosis; Diagnostic imaging; Electronic books